Strategic Reassurance in Institutional Contests : Explaining China's Creation of the Asian Infrastructure Investment Bank - Chen, Zheng (Taylor and Francis, 2018)
The Asian Infrastructure Investment Bank (AIIB) has been widely conceived as a Chinese effort to promote reforms of global financial governance. While the existing literature of contested multilateralism tends to focus on the problem of threat credibility, this article highlights the necessity of strategic reassurance in institutional contests. To facilitate incremental reforms of the existing order, rising powers like China need not only to pose credible challenge towards established institutions, but also to demonstrate their benign intentions and commitment to future cooperation. Besides revealing strength and resolve, the creation of a new multilateral regime helps rising powers to signal their self-restraints and reassure other powers. Consequently, the institutional configuration of new multilateral organizations involves a trade-off between the dual needs for threats and reassurance. Chinese behaviors in creating the AIIB can be explained through this framework.